Prevalence of Personality Disorders among Males and Females between the Ages of 15 and 65 in Yazd in 2017 - Nastaran Ahmadi; Parvaneh Rashidpour; Mohammadreza Mohammadi; Javad Aardeshirpay; Hosein Abouzari; Masoud Mirzaei; Amir Houshang Mehrparvar; Fatemeh Rismanian Yazdi; Mohammadhadi Farahzadi (Journal of Social Behavior and Community Health)
Background: Personality disorder is a type of mental disorder in which a rigid and unhealthy pattern of thinking, functioning, and behaving may be seen. A person with a personality disorder has trouble perceiving and relating to situations and people. Limited research has been done on the prevalence of personality disorders in Iran. This study aims at investigating the prevalence of personality disorders among males and females between the ages 15 and 65 in Yazd, Iran. Methods: The dataset for this cross-sectional study was extracted from a dataset of a national survey conducted on personality disorders of Iranians. The contents relevant to Yazd City were included here with a sample of 1827 people. Among the participants, 852 males and 975 females answered the personality disorders questionnaire (MILON). Results: Findings indicated that except histrionic and narcissistic patterns, the high rate of the rest of patterns was greater among females, which indicated that in most cases females significantly suffered higher clinical-related personality disorders. Moreover, personality disorders were more prevalent among females (29.8) compared to males (24.3). Conclusion: This area requires extensive investigation. More evidence is needed regarding the differential impact of personality disorders regarding men and women in other areas of Iran.